FEATURES OF CONDUCTING BEHAVIOR OF STUDENTS IN CONDITIONS OF ADAPTATION TO EDUCATIONAL ACTIVITY: CROSS-CULTURAL ASPECTS - Vladimir Solomonov (Вестник Северо-Кавказского федерального университета)
The article presents the results of the study of students' adaptation to the training group, the peculiarities of coping behavior of Russian and foreign students in the context of adaptation are considered. The analysis of the forms of coping mechanisms has made it possible to determine the basic coping strategies for Russian and foreign students that affect the adaptation to the training group and educational activities. Coping strategies are divided into three groups according to the degree of adaptive potentials: adaptive options, relatively adaptive options, nonadaptive options for coping behavior. The results of the study showed reliable differences between the cognitive indicators of coping behavior among students from Russia, near and far abroad.